Elective nodal irradiation provides a superior therapeutic modality for lymph node positivity esophageal squamous cell carcinoma patients receiving definitive radiotherapy versus involved-field irradiation. Issue 3 (January 2019) - Li, Qiaofang; Zhu, Shuchai; Li, Shuguang; Deng, Wenzhao
Abstract : Abstract: This retrospective study was conducted to evaluate the efficacy and safety of elective nodal irradiation (ENI) and involved-field irradiation (IFI) for esophageal squamous cell carcinoma (ESCC) patients treated with intensity-modulated radiotherapy (IMRT). From January 2006 to December 2012, 644 patients (ENI = 157, IFI = 487) with stage I to IVa ESCC (AJCC 2010) at our institution were analyzed. Propensity score matching (PSM) was used to identify 471 (ENI = 157, IFI = 314) well-balanced patients for comparison. Overall survival (OS) was the primary outcome of the study. After PSM, the median OS was 26.8 (95% confidence interval [CI], 17.9–35.7) for the ENI arm versus 21.5 (95% CI: 17.9–25.1) months in the IFI arm. The 1-, 3-, 5-year OS were 77.1%, 42.0%, and 26.1% for the ENI arm versus 73.2%, 32.2%, and 19.0% for the IFI arm ( P  = .020). ENI was a significant independent predictor of 5-year OS (1.301 [1.052–1.609]; P  = .015). Furthermore, patients with stage I/II ESCC or lymph node (LN) positivity in the ENI arm had significantly better 5-year OS than their counterparts in the IFI arm. In addition, for LN positivity patients treated with definitive radiotherapy alone, ENI tended to prolong OS compared with IFI ( P  = .035). The 2 arms were comparable in toxicities. Using IMRT, ENI is superior to IFI in improving OS of ESCC patients, with acceptable toxicities that were comparable to those to IFI, especially for LN positivity ESCC patients treated with definitive irradiation alone. These results should be confirmed in a large randomized study comparing these 2 modalities.